THE IMPACT OF PHYSICAL DOCUMENT UTILIZATION ON THE EFFECTIVENESS OF PUBLIC FINANCIAL ADMINISTRATION: A CASE STUDY OF BANK BJB KCP PEMKOT BANDUNG 1 - Alya Ruina Antalina; Silvi Erli Nurhavilah; Wafiq Meilani Walikarna (JAT : Journal Of Accounting and Tax, 2025)
Although the use of physical documents in administration has advantages in terms of legality and certain security aspects, on the other hand, it often raises various issues such as delays in the verification process due to manual input, the risk of document loss, as well as inefficiencies in time and cost. In fact, the development of digital systems somewhat encourages the transition towards a more effective and efficient financial administration system, but the reality is that many institutions use different applications that are not integrated with each other, and there are even some institutions that do not use digital systems, resulting in data duplication, inconsistency of information, and slowing down decision-making processes. Assessing the inefficiency of the impact of a digital system that is not yet evenly distributed, the digital system is implemented by government institutions which become the center of public financial administration, so that public financial administration is more structured by the government and reduces the risks from various parties. The overall use of the system can expedite the administration process as it is more effective and efficient, and the use of the system can also minimize the use of physical documents as examined through causal-comparative research methods. Public financial administration actually uses documents that slow down the administration process; manual verification, archiving of files, and the transfer of documents between units pose risks of duplication as well as delays. This finding is in line with a study at Bank BJB KCP Pemkot Bandung 1 which states that although physical documents are still procedurally used, the manual system negatively impacts the speed of administrative services.